Spiritual Techniques to Reduce Anxiety in Chronic Kidney Disease Patients Undergoing Haemodialysis: A Study on SQEFT - Sawiji, Sawiji; Said, Faridah Mohd; Aljaberi, Musheer Abdulwahid; Utomo, Rahmat Prasetyo; Huda, Akhmad (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
This study explores the effectiveness of spiritual techniques, specifically the Qur'anic Emotional Freedom Technique (SQEFT), in reducing anxiety among chronic kidney failure patients undergoing haemodialysis. A quasi-experimental one-group pre-test post-test design was employed on 29 patients over 30 days, with sessions held twice weekly. Anxiety levels, assessed using the Hospital Anxiety and Depression Scale (HADS), showed a significant reduction after the intervention (p = 0.000). These findings suggest that SQEFT, as a spiritual technique, offers a promising non-pharmacological approach to managing anxiety in haemodialysis patients. Future studies are encouraged to explore its broader psychological benefits and long-term impact on patient well-being.